Intraoperative Optical Coherence Tomography in Idiopathic Macular Epiretinal Membrane Surgery - Mao ZQ; Wu HX; Fan HM; Li G; You ZP; Tan YY (International Journal of General Medicine, 2022)
Zi-Qing Mao,1 Hong-Xi Wu,1 Hui-Min Fan,1 Gen Li,2 Zhi-Peng You,1 Yun-Yu Tan1 1Department of Ophthalmology, Affiliated Eye Hospital of Nanchang University, Nanchang, 330006, People’s Republic of China; 2Department of Ophthalmology, Zhangshu People’s Hospital, Zhangshu, 331299, People’s Republic of ChinaCorrespondence: Zhi-Peng You, Department of Ophthalmology, Affiliated Eye Hospital of Nanchang University, Nanchang, 330006, People’s Republic of China, Email 1289560272@qq.comObjective: To evaluate the feasibility and practicability of intraoperative optical coherence tomography (IOCT) in the surgery of idiopathic macular epiretinal membrane (IMM) without internal limiting membrane staining in all patients.Methods: Patients were selected from July 2018 to June 2020, and 32 patients (32 eyes) with IMM were operated with the use of IOCT. All patients underwent standard 23g vitrectomy. The internal limiting membrane was peeled off if there were obvious retinal folds. Intraoperative and postoperative complications, macular microstructural changes, and integrity of the detached membranes were recorded. The preoperative and postoperative best corrected visual acuity were compared.Results: The macular epiretinal membrane was completely removed in 75% (24 eyes) patients without internal limiting membrane staining, and in 15.6% (5 eyes) patients with combined internal limiting membrane stripping. The “starting point” of macular epiretinal membrane stripping was found in 75% (24 eyes), and the time required to find the best starting point ranged from 28s to 140s (mean 66 ± 15s). At 3 months after operation, 96.8% of the patients had stable or improved BCVA (p < 0.05). The central macular thickness of the affected eyes decreased significantly at 1 and 3 months after operation (p < 0.05).Conclusion: IOCT can significantly reduce the use of internal limiting membrane staining in idiopathic macular epiretinal membrane surgery, and it is safe, feasible and practical in idiopathic macular epiretinal membrane surgery without internal limiting membrane staining in all patients.Keywords: intraoperative optical coherence tomography, epiretinal membrane, inner limiting membrane